Bringing to Life the Qualities of a Meaningful Transformative Education - Melissa Glackin; Kate Greer (Australian Journal of Environmental Education)
This paper shares a heuristic to support thinking about meaningful transformative education within the context of the contemporary environmental and social crisis. We describe the context of this work and explore the epistemological foundations for this model, which has been evolving and guiding our research and teaching and which underpins the six qualities of meaningful transformative education. The qualities are being open to alternative visions of the future and alternative approaches to education, accepting and embracing complexity, incorporating multiple types of knowledge, reorienting towards justice, developing ecological worldviews and supporting students to bring about systemic change. We also present a series of illustrative vignettes, informed by real-world practices of schools in England, which bring these qualities to life. The vignettes and subsequent discussion highlight possibilities and challenges for enacting a meaningful transformative education in schools.